Meta-analisis penerapan model pembelajaran inkuiri terbimbing dalam pembelajaran fisika - Revi Febrina Sari; Silvi Yulia Sari; Yenni Darvina; Asrizal Asrizal (Universitas Negeri Padang, 2020)
This study aims to determine the effect of guided inquiry learning models in physics learning. The method used is a meta-analysis that summarizes and analyzes research results that have been published nationally and internationally relating to the guided inquiry model in physics learning. The analysis sample was twenty-six journals published in the last 10 years. Writing instruments in the form of sheets coding that encapsulate data and journal information. The results of this study are the guided inquiry learning model based on the level of education are both effectively used both at the senior high school level and junior high school level withcategories effect size large. Viewed from the learning material, the guided inquiry learning model is more effectively used in sound resonance material. Meanwhile, based on the dependent variable used, the value of effectiveness with a high category is found inabilities Higher Order thinking Skills students'(HOTS). Then it can be concluded that the guided inquiry learning model on physics learning is very effective to be used in supporting the learning process especially the ability of Higher Order thinking Skills (HOTS) students.